The use of darbepoetin alpha in infants - A. V. Shchegolev; G. Z. Sufianova; A. A. Sufianov; N. E. Ivanova; M. S. Khlestkina (Сеченовский вестник, 2019)
Among the somatic pathology in young children, the most common is anemic syndrome. Until recently, the commonest method for correction of anemia was hemotransfusion, which allows to restore normal hemoglobin quickly, but has the high risk of complications. The main disadvantage of this method is the short - term positive eﬀect and necessity of repeating donor red blood cell transfusions to prevent rapid progression of anemia. The currently available alternative is the use of an erythropoiesis - stimulating agent, which increases the level of hemoglobin and red blood cells in the blood by stimulating of erythropoiesis in the bone marrow. Modern erythropoiesis - stimulating agent and anti - anemic drug, registered in Russian Federation, is darbepoetin alpha. When developing this drug, a new approach was used to increase the number of sialic acid residues and the degree of glycolysis. This helped to achieve an optimal ratio between the activity and the half - life period of the drug and made possible to prescribe it with longer intervals between injections. Currently, there is evidence of eﬀective and safe use of darbepoetin alpha in premature infants with low body weight, anemia, encephalopathy and chronic kidney disease.